Re-Extension of 200 MW Turbine Cast Casing Service - Chernousenko, O.Yu.; Ryndyuk, D.V.; Peshko, V.A. (Проблеми машинобудування, 2019)
This paper assesses the residual life of casings on the basis of three-dimensional models of the K-200-130-3 steam turbine high-pressure (HP) and intermediate- pressure (IP) cylinder casings. In doing so, the paper takes into account the actual operating conditions according to the damage data obtained from the results of inspecting the power equip-ment metal condition during preventive maintenance overhauls.